Zwitterionic coating assisted by dopamine with metal-phenolic networks loaded on titanium with improved biocompatibility and antibacterial property for artificial heart - Meng, Lingwei; Huang, Chuangxin; Liu, Xin; Qu, Hongyi; Wang, Qiuliang (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Titanium (Ti) and Ti-based alloy materials are commonly used to develop artificial hearts. To prevent bacterial infections and thrombus in patients with implanted artificial hearts, long-term prophylactic antibiotics and anti-thrombotic drugs are required, and this may lead to health complications. Therefore, the development of optimized antibacterial and antifouling surfaces for Ti-based substrate is especially critical when designing artificial heart implants. Methods: In this study, polydopamine and poly-(sulfobetaine methacrylate) polymers were co-deposited to form a coating on the surface of Ti substrate, a process initiated by Cu2+ metal ions. The mechanism for the fabrication of the coating was investigated by coating thickness measurements as well as Ultraviolet–visible and X-ray Photoelectron (XPS) spectroscopy. Characterization of the coating was observed by optical imaging, scanning electron microscope (SEM), XPS, atomic force microscope (AFM), water contact angle and film thickness. In addition, antibacterial property of the coating was tested using Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) as model strains, while the material biocompatibility was assessed by the antiplatelet adhesion test using platelet-rich plasma and in vitro cytotoxicity tests using human umbilical vein endothelial cells and red blood cells. Results and discussion: Optical imaging, SEM, XPS, AFM, water contact angle, and film thickness tests demonstrated that the coating was successfully deposited on the Ti substrate surface. The biocompatibility and antibacterial assays showed that the developed surface holds great potential for improving the antibacterial and antiplatelet adhesion properties of Ti-based heart implants.